Analysis of antibiotic residues in raw bovine milk and their impact toward food safety and on milk starter cultures in cheese-making process. (September 2020) - Chiesa, Luca Maria; DeCastelli, Lucia; Nobile, Maria; Martucci, Francesca; Mosconi, Giacomo; Fontana, Mauro; Castrica, Marta; Arioli, Francesco; Panseri, Sara
Abstract: Antibiotics are widely used in livestock production as disease treatment, prevention and improve feeding efficiency. In this study three screenings and a multiclass method by Liquid Chromatography tandem Mass High Resolution Spectrometry (LC-HRMS) were developed and used to evaluate the antimicrobial substance incidence in 254 raw bovine milks involved in PDO cheese production in Northern Italy. The LC-HRMS results were compared to assess the frequency of false and negative results in term of reliability of screening methods. An investigation in relation to the quantified residues evaluating their possible negative impact on milk starter cultures in a simulated cheese-making process was presented. Lincomycin residues were observed in 30 samples, with 11.8% frequency and 17.29 ppb as mean value below its MRL. Three samples showed oxytetracycline respectively at 15.05, 0.82 and 1.59 ppb and two cefapirin and spyramycin at trace level. False positives with an acceptable frequency were observed by using the 3 kits confirming this approach useful for monitoring plans. Considering lincomycin, negative effect was demonstrated toward lactic acid bacteria activity in term of bacteria counts, pH and acidity during cheese making simulation. This represents a critical aspect considering both the economic value of PDO cheeses and the antibiotic resistance diffusion. Highlights: Antibiotic usage in animals may leave antibiotic residues in foodstuffs such as milk, egg and meat. Screening test give great advantages in routine control. Lincomycin was detected in several milk sample below its MRL. Lincomycin led a negative impact on lactic acid bacteria.